2017
DOI: 10.1002/app.45955
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of morphology, ferroelectric, and mechanical properties in poly(vinylidene fluoride)–poly(vinylidene fluoride‐trifluoroethylene) blends

Abstract: Considering the complementary properties of poly(vinylidene fluoride) (PVDF) and poly(vinylidene fluoride‐trifluoroethylene) [P(VDF‐TrFE)], it appears that their blends have the potential to be promising candidates for device applications. We report the evolution of morphology, ferroelectric, and mechanical properties (modulus and hardness) and their dependence on preparation temperature for PVDF–P(VDF‐TrFE) blends. From ferroelectric hysteresis measurements it was found that P(VDF‐TrFE) rich blends treated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…PVDF is one promising functional polymer extensively used in applications ranging from energy transductions , to filtration membranes , and nonvolatile FE-RAMs , to space mirrors . PVDF is widely studied for its outstanding electroactive properties, chemical inertness, and high dielectric constant compared with other polymers. , The physical properties of PVDF and content of different polymorphic phases can be controlled by varying synthesis conditions. , From the above discussion, it becomes apparent that electrical properties and polymorphism in PVDF have been studied quite extensively. The Mechanical properties of materials play a pivotal role in determining the function and realizing smooth operation of devices.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…PVDF is one promising functional polymer extensively used in applications ranging from energy transductions , to filtration membranes , and nonvolatile FE-RAMs , to space mirrors . PVDF is widely studied for its outstanding electroactive properties, chemical inertness, and high dielectric constant compared with other polymers. , The physical properties of PVDF and content of different polymorphic phases can be controlled by varying synthesis conditions. , From the above discussion, it becomes apparent that electrical properties and polymorphism in PVDF have been studied quite extensively. The Mechanical properties of materials play a pivotal role in determining the function and realizing smooth operation of devices.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of materials are strongly correlated with the underlying microstructure. , For example, in our previous study, we found that the hardness of PVDF-P­(VDF-TrFE) blends is intimately linked to their morphology. The hardness values show a marked decline when the blend morphology changes into fiber-shaped crystals . Therefore, understanding crystallization in polymers becomes imperative for tailoring their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations